Media Edukasi Dental Hunt Treasure Map Sebagai Upaya Meningkatkan Pengetahuan Siswa Kelas V di MI Miftahul Falah Sinanggul Wilayah Kerja Puskesmas Mlonggo, Jepara Dental Hunt Treasure Map Educational Media as an Effort to Improve Knowledge Among Fifth-Grade Students at MI Miftahul Falah Sinanggul, Mlonggo Health Center Area, Jepara - Anita Pujianti; Endah Aryati Ekoningtyas (ABDIGI : JURNAL PENGABDIAN MASYARAKAT KESEHATAN GIGI, 2025)
Oral health is an integral part of general health, yet many elementary school children have low levels of knowledge regarding proper oral care. Preliminary findings at MI Miftahul Falah Sinanggul showed that most fifth-grade students were categorized as having poor oral health knowledge. This study aimed to evaluate the effectiveness of the Dental Hunt Treasure Map, an interactive game-based educational media, in improving students’ knowledge of oral health. A pre–posttest design was applied in which students’ knowledge was measured using a structured questionnaire before and after the intervention. The intervention involved the use of the Dental Hunt Treasure Map, designed to deliver oral health messages through engaging tasks and activities. Data were analyzed to assess the changes in knowledge scores. The results showed a significant increase in knowledge after the intervention, with more students achieving good knowledge levels and fewer remaining in the poor category. These findings indicate that interactive, game-based educational tools are effective in supporting oral health education among school-aged children. In conclusion, the Dental Hunt Treasure Map proved to be an effective medium for increasing students’ knowledge of oral health and has potential as an attractive, practical, and easily understood alternative for school-based health promotion programs.